Gene therapy as an emerging treatment for Scn2a mutation-induced autism spectrum disorders - Arkadeep Ghosh; Nitin Nadella; A Paula Monaghan-Nichols; Xiang-Ping Chu (Fundamental Research)
Autism spectrum disorder (ASD) is a complex neurological and developmental disorder that affects how a person acts, communicates, learns, and interacts with others. It affects the structure and function of the brain and nervous system. How ASD is caused remains uncertain and there is no effective treatment for this disorder. Searching for new technologies for treatment of this disorder becomes a priority. Genetic alterations have been implicated in the generation of this disorder. One of the most promising genes for potential treatment of ASD is sodium voltage-gated channel alpha subunit 2 gene (SCN2A). SCN2A, encoding the neuronal voltage-gated Na+ channel NaV1.2, is one of the most commonly affected loci linked to ASD. Here, we discuss the implications of loss of function (LOF) mutations in SCN2A and the potential efficacy of gene therapy by highlighting the usage of CRISPR restoration of various Scn2a-insufficiencies. Various therapeutics exist that can be extrapolated to address the needs of Scn2a LOF induced ASD. The current treatment that exists for ASD can be seen as outdated in comparison to the advent of new technologies that build upon CRISPR. Due to complications in treatment of ASD, genetic therapies may induce alterations such as insertion–deletion mutations, which may lead to further complications along with a negative public outlook on CRISPR technologies. Gene therapy can be applied to ASD but much work is yet to be done in order to address both biochemical and ethical considerations.